2022
DOI: 10.1002/npr2.12228
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of lamotrigine for persistent depressive disorder: A case report

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Used off-label for bipolar disorder [179]. Could potentially offer an effective option in addressing individuals with treatment-resistant persistent depressive disorder, being a viable substitute for the combination of antidepressant and benzodiazepine therapies in this disorder [180].…”
Section: Lamotriginementioning
confidence: 99%
“…Used off-label for bipolar disorder [179]. Could potentially offer an effective option in addressing individuals with treatment-resistant persistent depressive disorder, being a viable substitute for the combination of antidepressant and benzodiazepine therapies in this disorder [180].…”
Section: Lamotriginementioning
confidence: 99%
“…Lamotrigine has advantages beyond its usage in treating epilepsy and bipolar disorder, according to findings from two blinded studies and many open trials for individuals with severe mental disability and refractory epilepsy [ 59 ]. Overall, while lamotrigine was originally developed for the treatment of epilepsy, its unique mechanism of action and favorable effects on psychological well-being have made it a promising option for the management of bipolar disorder and other conditions [ 60 ].…”
Section: Overview Of Antiepileptic Drugsmentioning
confidence: 99%
“…This drug selectively binds and inhibits voltage-gated sodium channels, characterized by being an anti-seizure/anti-epileptic drug, also used in bipolar I disorder [ 31 ]. In persistent depression, lamotrigine was also reported to be possibly effective for the treatment of individuals with persistent depression who were antidepressant resistant [ 32 ]. A meta-analysis also concluded that this drug was also better than the placebo in improving unipolar and bipolar depressive symptoms [ 33 ].…”
Section: Introductionmentioning
confidence: 99%